The Systematic Work Up to Identify Etiology of Non-immune Hydrops Fetalis: A perspective view of pathologist - Patou Tantbirojn (The Royal Thai College of Obstetricians and Gynaecologists, 2020)
Non-immune hydrops (NIH) is an important condition in health service. Many etiologies of NIH have been described, but the definite cause of NIH in many cases is still reported as "unknown". This finding may be partly explained by the inadequate investigation. The article summarized the possible etiology of NIH and the needed investigation to establish cause of NIH from the view of pathologist.